Efficacy of electro-acupuncture in postpartum with diastasis recti abdominis: A randomized controlled clinical trial - Liu, Yan; Zhu, Ying; Jiang, Liyuan; Lu, Chao; Xiao, Lijuan; Wang, Ting; Chen, Jiayu; Sun, Li; Deng, Lujun; Gu, Meiyu; Zheng, Tingting; Feng, Min; et al. (Frontiers in Public Health, 2022)
Background: Electroacupuncture (EA) has promising effects on diastasis rectus abdominis (DRA), defined as a separation of the two muscle bellies of rectus abdominis. To study there is scant knowledge on scarce high-quality evidence. Objective: To evaluate the long-term efficacy and safety of EA in treating DRA during postpartum. It was assumed that the improvement of DRA was more obvious in EA group than in the control group. Intervention:110 participants were randomly assigned in a 1:1 ratio to a control group with no EA intervention (n = 55), and EA group (n = 55). Ten sessions of EA combined with physical exercise or only physical exercise over two weeks, with 26-weeks follow-up after treatment. Results: A total of 110 maternal (55 in each group) were recruited. The mean difference in IRD from baseline to week 2 and week 26 in all states of the two groups were reduced compared with those before treatment, with statistical significance (P<0.05). The mean of IRD at the horizontal line of umbilicus in end-expiratory state was smaller in the EA group than in the control group, but the difference was not statistically significant (P>0.05) at week 2. The mean of IRD at the horizontal line of umbilicus in head-up and flexed knee state was smaller in the EA group than in the control group, and the difference was statistically significant (P<0.05) at week 26. Five (9.1%) and thirteen (23.64%) adverse events were reported in EA and control groups, respectively. No serious adverse events were reported. Limitation: Frequency intensity of EA parameters was selected 4-6 because of individual tolerance differences. Conclusion: EA is an effective approach to improve IRD, electromyographic evaluation of the pelvic floor, BMI, elastic of linea alba, paraumbilical SAT, symptoms of DRA, with durable effects 26 weeks after treatment.